Electrocoagulation using aluminum electrodes as a sustainable and economic method for the removal of kinetic hydrate inhibitor (polyvinyl pyrrolidone) from produced wastewaters - Al-Marri, Jawaher S.; Abouedwan, Aisha B.; Ahmad, Mohammad I.; Bensalah, Nasr (Frontiers in Water, 2023)
Electrocoagulation is a water treatment technology capable to remove a variety of organic pollutants from water. It is advantageous compared to chemical coagulation due to the controlled dissolution of coagulants by regulating the current density and pH.In this work, the removal of kinetic hydrate inhibitor (KHI) (polyvinyl pyrrolidone, PVP) from water by electrocoagulation using Al electrodes was investigated. The effects of several experimental conditions including the nature of the supporting electrolyte, the current density, and the initial pH value on the electrochemical dissolution of aluminum was evaluated. The findings of the experiments revealed that both chemical and electrochemical dissolution play important roles in the generation of hydroxo-aluminum species. Corrosion studies demonstrated that the presence of chloride ions in water promotes aluminum dissolving via pitting corrosion, whereas the presence of phosphate ions inhibits aluminum corrosion by the deposition of a thick passive layer of aluminum hydroxide/phosphate on the metal surface. The theoretical and experimental amounts of aluminum, increase linearly with increasing specific electrical charge for Q< 2.5 Ah/L, which correlates well with Faraday's Law. The removal of KHI from 0.1M NaCl aqueous solutions by electrocoagulation using aluminum electrodes achieved high removal efficiency in terms of total organic carbon (TOC) up to 95%. TOC decay during galvanostatic electrolysis confirmed the removal of KHI molecules by Alelectrocoagulation at different current densities and pH conditions. The primary mechanism involved in eliminating KHI from water by electrocoagulation using Al electrodes includes mainly the adsorption of PVP molecules on the surface of Al(OH)3 flocs and their enmeshment inside the solid coagulants.